2020
DOI: 10.1002/esp.4818
|View full text |Cite
|
Sign up to set email alerts
|

The impact of internal waves on upper continental slopes: insights from the Mozambican margin (southwest Indian Ocean)

Abstract: Evidences of sedimentation affected by oceanic circulation, such as nepheloid layers and contourites are often observed along continental slopes. However, the oceanographic processes controlling sedimentation along continental margins remain poorly understood. Multibeam bathymetry and high‐resolution seismic reflection data revealed a contourite depositional system in the Mozambican upper continental slope composed of a contourite terrace (a surface with a gentle seaward slope dominated by erosion) and a plast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 66 publications
0
45
0
Order By: Relevance
“…We suggest that contourite terraces may have been initiated by erosion on the slope generated by the (paleo) Malvinas Current that progressively cut the slope landwards, widening the contourite terrace with time. The fact that the Argentine contourite terraces are much wider and flatter than other terraces observed for instance in the Mediterranean Sea (Ercilla et al, 2016;Miramontes et al, 2019), along the Mozambican margin (Thiéblemont et al, 2019;Miramontes et al, 2020) and in the Makassar Strait (Brackenridge et al, 2020) could be related to the higher speed of near-bottom currents as part of the Malvinas Current. The particular flat morphology with an abrupt edge of the terraces along the Argentine margin may favour the formation of internal waves at the terrace edge, in a similar way as at the shelf break (Jackson et al, 2012) that could also favour sediment transport and erosion along the terrace.…”
Section: Terrace Formationmentioning
confidence: 89%
See 2 more Smart Citations
“…We suggest that contourite terraces may have been initiated by erosion on the slope generated by the (paleo) Malvinas Current that progressively cut the slope landwards, widening the contourite terrace with time. The fact that the Argentine contourite terraces are much wider and flatter than other terraces observed for instance in the Mediterranean Sea (Ercilla et al, 2016;Miramontes et al, 2019), along the Mozambican margin (Thiéblemont et al, 2019;Miramontes et al, 2020) and in the Makassar Strait (Brackenridge et al, 2020) could be related to the higher speed of near-bottom currents as part of the Malvinas Current. The particular flat morphology with an abrupt edge of the terraces along the Argentine margin may favour the formation of internal waves at the terrace edge, in a similar way as at the shelf break (Jackson et al, 2012) that could also favour sediment transport and erosion along the terrace.…”
Section: Terrace Formationmentioning
confidence: 89%
“…Thus, other processes have to be taken into consideration. Previous research reported that internal waves can form sediment waves and dunes (Hand, 1974;Reeder et al, 2011;Droghei et al, 2016;Ribó et al, 2016;Reiche et al, 2018;Yin et al, 2019;Miramontes et al, 2020). Internal waves can propagate at density discontinuities and have been previously proposed as a cause for the development of the Ewing Terrace and the La Plata Terrace (Hernández-Molina et al, 2009;Preu et al, 2013).…”
Section: Sediment Wavesmentioning
confidence: 97%
See 1 more Smart Citation
“…We suggest that contourite terraces may have been initiated by erosion on the slope generated by the action of two water masses and their interphase trough time, being the (paleo) Malvinas Current one of the key factors that progressively cut the slope landwards, widening the contourite terrace with time. The fact that the Argentine contourite terraces are much wider and flatter than other terraces observed for instance in the Mediterranean Sea (Ercilla et al, 2016;Miramontes et al, 2019), along the Mozambican margin (Thiéblemont et al, 2019;Miramontes et al, 2020) and in the Makassar Strait (Brackenridge et al, 2020) could be related to the higher speed of near-bottom currents as part of the Malvinas Current and the long time period of erosion (since the opening of the Drake Passage). The particular flat morphology with an abrupt edge of the terraces along the Argentine margin may favour the formation of internal waves at the terrace edge, similar to those observed at the shelf break (Jackson et al, 2012), that could also favour sediment transport and erosion along the terrace.…”
Section: Terrace Formationmentioning
confidence: 90%
“…The upper continental slope of the Mozambican margin consists laterally of: a) a convex slope with a plastered drift and a contourite terrace to the southwest, offshore the Zambezi delta (Figs. 1B and 2A;Thiéblemont et al, 2019); and b) a concave slope with a plastered drift and a dune field, 50 km further northeast or west offshore the Zambezi delta (Miramontes et al, 2020b). This work focuses on the sector between the distal part of that contourite terrace and the deeper adjacent plastered drift (core MOZ4-CSF19; Fig.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%